1994
DOI: 10.1007/bf00405700
|View full text |Cite
|
Sign up to set email alerts
|

Exposure monitoring and health effect studies of workers occupationally exposed to cyclohexane vapor

Abstract: A survey was conducted in the second half of a working week on 33 women who either applied glue (with cyclohexane as an almost exclusive solvent component) or worked in the vicinity of glue application. Carbon cloth-equipped diffusive samplers were used for personal measurement of time-weighted average intensity of exposure to the solvent. The geometric mean and the highest cyclohexane concentration observed in air were 27 ppm and 274 ppm, respectively. Concentrations of cyclohexanol in urine samples and cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
1
23
1
2
Order By: Relevance
“…The validation apparently deserves further confirmation through larger scale factory surveys. With two assumptions that the rate of absorption of toluene in the lungs is about 50% 28) and that the respiration rate is 10 l/min 29) , exposure to toluene at 50 ppm will result in an absorption of 940 µg toluene /min, when calculated as 50 ppm (or 188 mg/m 3 ) × 10 ×10 -3 m 3 /min × 50/100. According to the calculated regression line in Table 2, toluene excreted into urine as BeOH at the end of an 8-h toluene exposure at 50 ppm will be 85 µg/l [= 1.7 × 50] or 85 ng/min, assuming that urine out-put volume is 1 ml/min 30) .…”
Section: Discussionmentioning
confidence: 99%
“…The validation apparently deserves further confirmation through larger scale factory surveys. With two assumptions that the rate of absorption of toluene in the lungs is about 50% 28) and that the respiration rate is 10 l/min 29) , exposure to toluene at 50 ppm will result in an absorption of 940 µg toluene /min, when calculated as 50 ppm (or 188 mg/m 3 ) × 10 ×10 -3 m 3 /min × 50/100. According to the calculated regression line in Table 2, toluene excreted into urine as BeOH at the end of an 8-h toluene exposure at 50 ppm will be 85 µg/l [= 1.7 × 50] or 85 ng/min, assuming that urine out-put volume is 1 ml/min 30) .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of cyclohexane to cyclohexanone has been described (Elliott et al 1959, Mráz et al 1994, Yasugi et al 1994 and is shown in Figure 1. Data for the biotransformation of cyclohexane in man are to date inadequate.…”
Section: Metabolismmentioning
confidence: 92%
“…Mráz et al 1994, Mutti et al 1981, Ong et al 1991, Perico et al 1999, Trabs 1999, Walter et al 1999, Yasugi et al 1994. In particular the field study of Perico et al (1999), a simulation model of the same author based on data of Perbellini et al (1988Perbellini et al ( , 1990 and Mráz et al (1994), and laboratory studies of Mráz et al (1998), Trabs (1999) and Walter et al (1999) can be used as the basis for the evaluation of a BAT value for cyclohexane.…”
Section: Exposure and Effectsmentioning
confidence: 99%
“…Der Metabolismus von Cyclohexan zu Cyclohexanon ist beschrieben (Elliott et al 1959;Mráz et al 1994;Perbellini und Brugnone 1980;Yasugi et al 1994) …”
Section: Metabolismusunclassified
“…Mráz et al 1994Mráz et al , 1998Mutti et al 1981;Ong et al 1991;Perbellini et al 1980;Perbellini und Brugnone 1980;Perico et al 1999;Walter et al 1999;Yasugi et al 1994). Als Grundlage zur Evaluierung eines BAT-Wertes für Cyclohexan lassen sich insbesondere die Feldstudie von Perico et al (1999), ein Simulationsmodell des gleichen Autors, basierend auf Daten von Perbellini et al (1988) und Mráz et al (1994, sowie Laborstudien von Mráz et al (1998), bzw.…”
Section: Belastung Und Beanspruchungunclassified